Teachers’ Pedagogical Strategies in English Instruction at MAS NW Senyir, Lombok Timur Academic Year 2023/2024 - Rianda Wijaya (Innovative Pedagogy and Education Studies, 2024)
This study aims to explore teachers’ pedagogical strategies in English instruction at MAS NW Senyir, Lombok Timur, during the academic year 2023/2024. A qualitative research approach with a descriptive case study design was employed. The participants of this study consisted of English teachers and selected students at the school. Data were collected through classroom observations, semi-structured interviews, and document analysis, including lesson plans and teaching materials. The data were analyzed using qualitative data analysis procedures involving data reduction, data display, and conclusion drawing. The findings reveal that English teachers at MAS NW Senyir applied various pedagogical strategies, such as communicative language teaching, cooperative learning, and contextual teaching approaches, to enhance students’ engagement and language skills. However, the implementation of these strategies faced several challenges, including limited instructional time, students’ diverse proficiency levels, and restricted exposure to English outside the classroom. The study concludes that the effective use of pedagogical strategies requires adaptive teaching practices that align with students’ needs and the school context. These findings provide practical implications for improving English instruction and teacher professional development in Islamic senior high schools.